ANALISIS KOMPARATIF PENDAPATAN USAHATANI PADI SAWAH YANG MENGGUNAKAN PUPUK BERIMBANG DAN TIDAK BERIMBANG DI DESA BALUASE KABUPATEN SIGI - Taher, Edi Anwar; Lamusa, Arifuddin (AGROTEKBIS, 2016)
This study aims to determine the total costs, production volume, sales price and the amount of farm income in the village paddy Baluase South Dolo Sigi Districts. The research was conducted in January and February 2015. The Respondent is done by simple random sampling method (Simple Random Sampling), dengan consideration the number of respondents who were taken in the study of 20 farmers. The analysis used in this study is an analysis of income. The results showed that the average/ha income received by farmers for rice farming rice fields where the use of balanced fertilizer sebesar average income of Rp 20.91405 million/ha, while the average income does not use a balanced fertilizer Rp 8.2358 million /Ha. By means paddy rice farming which uses balanced fertilizer gave the comparison of real incomes by not using balanced fertilizer.Â Key Words: Comparative analysis of revenue paddy balanced and unbalanced fertilizer.